Le nuove identità culturali glocali: dagli Italiani agli Italici (Glocalism: Journal of Culture, Politics and Innovation, 2017)
Globalisation is constantly redefining the processes of individual and collective identity construction. We are experiencing a profound change of era. As many important sociologists have said, we are facing a change of our identity and our social relations in everyday life. Time and space are changing, proximity is our local dimension, but we are immersed in the global flows. Processes of deterritorialization and virtualisation are widespread and characteristic of this new era, profoundly different from the modern era, where territory was so strongly linked to sovereignty and citizenship. Nowadays the crisis of the idea of the modern nation state is reflected by the difficulty in keeping the same meanings to the same expressions. This creates consequences for the Italian community in the world and their changes – the fundamental theme of our research – which take on new identities and functions. In particular we face the new idea of a glocal and cultural identity called Italicity, a sort of Italic commonwealth.
Keywords: Glocalism; Nation-State; Postmodernity; Culture; Network